Performance Anxiety and Self Efficacy among Hockey Players (International Journal of Food and Nutritional Sciences, 2022)
Performance anxiety not only controls one’s ability but stops the best performance. It makes an athlete to feel mentally weak and decreases the level of self-efficacy. Albert Bandura (1977) A person with high Self Efficacy views challenges as things that are supposed to be mastered rather than threats to avoid. The study examines the relationship of Performance Anxiety and Self Efficacy among Hockey Players. To assess and identify the gender differences in Performance Anxiety and Self Efficacy among players. The Sample consists of 30 Hockey Players who were selected from Shanthi Nagar Hockey Stadium, Bangalore. The Sample includes 15 male and 15 female hockey players with age range of 15-25 years. They were administered with Performance Anxiety and Self Efficacy scales. The findings revealed that there were significant differences existed between male and female hockey players in Performance Anxiety Dimensions such as Somatic, Worry and Concentration Disruption and in the level of Self Efficacy among male and female hockey players.Male Hockey Players had expressed more worries, problems with concentration and easily disturbed with external obstacles when compared to Female Hockey Players. Female Hockey Players had better Self Efficacy compared to Male Hockey Players. It really shows that the Hockey Players needs to be given Psychotherapy to manage the performance anxiety and Cognitive Behaviour Therapy to enhance self-efficacy. The study provides a focus point for improving their achievement and excellence.